2011
DOI: 10.1139/x11-086
|View full text |Cite
|
Sign up to set email alerts
|

Linking climate, gross primary productivity, and site index across forests of the western United States

Abstract: Assessing forest productivity is important for developing effective management regimes and predicting future growth. Despite some important limitations, the most common means for quantifying forest stand-level potential productivity is site index (SI). Another measure of productivity is gross primary production (GPP). In this paper, SI is compared with GPP estimates obtained from 3-PG and NASA’s MODIS satellite. Models were constructed that predict SI and both measures of GPP from climate variables. Results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(68 citation statements)
references
References 37 publications
5
55
0
1
Order By: Relevance
“…We computed the variable importance measure of each predictor as given as the average percent change (before and after permutation) in the OOB error when the variable is permuted, while all others are retained unchanged. For model optimization, the backward variable selection approach [10] was applied minimizing the RMSE and maximizing the pseudo R 2 .…”
Section: Optimizing Size Of Catchment Areas (Ca) For Estimating Simentioning
confidence: 99%
See 1 more Smart Citation
“…We computed the variable importance measure of each predictor as given as the average percent change (before and after permutation) in the OOB error when the variable is permuted, while all others are retained unchanged. For model optimization, the backward variable selection approach [10] was applied minimizing the RMSE and maximizing the pseudo R 2 .…”
Section: Optimizing Size Of Catchment Areas (Ca) For Estimating Simentioning
confidence: 99%
“…Geocentric approaches have been used as a basis for estimating SI or other measures of forest productivity and involve relating SI to various direct and/or indirect environmental factors [1]. Many studies have revealed environmental predictors of SI, using edaphic [2][3][4][5], topographic [6][7][8], and/or climatic [9][10][11] variables. Geocentrically-based (biophysical) SI models are independent from stand age and structure, usually have satisfactory prediction power and, therefore, provide tools that can effectively inform forest management.…”
Section: Introductionmentioning
confidence: 99%
“…Since site index is rarely measured in the Acadian Region and detailed soil maps do not exist for much of the region, CSI was derived based on the geographical location of sample plots. This index was based on 1-km 2 climate normals from 1960 to 1991 and an empirically derived relationship with observed site index (Weiskittel et al 2011a). We also tried the Hopkins (1938) Index to transform elevation, latitude, and longitude.…”
Section: Addition Of Covariatesmentioning
confidence: 99%
“…The site index is assumed to be constant over time, and thus included as a driving variable in forest growth and yield models. In reality, the site index often varies greatly due to changes in the genetic make-up of stands, climatic conditions and management practices (Monserud & Rehfeldt 1990, Valentine 1997, Weiskittel et al 2011). Empirical models have been developed to estimate the site index from climate, soil and vegetation information, thus allowing the possibility of predicting changes in the site index, forest growth and forest yield under climate change (McKenney & Pedlar 2003, Nigh et al 2004, Monserud et al 2006, 2008, Albert & Schmidt 2009, Aertsen et al 2011, Nothdurft et al 2012.…”
Section: Introductionmentioning
confidence: 99%